Utilization of RNN Chatbots for Midwifery Education for Pregnant Women at Rantauprapat City Community Health Centers - Fadillah, Riszki; Tanjung, Rani Darma Sakti; Tusakdiyah, Halimah; Jolyarni D, Novica; Purwanto, Juni (PT Inovasi Pratama Internasional, 2025)
The application of information technology in the healthcare sector has been rapidly advancing with the development of artificial intelligence. One of its potential applications is the use of chatbots powered by the Recurrent Neural Network (RNN) algorithm to enhance maternal health education access for pregnant women. Although health information is increasingly accessible, pregnant women often face challenges in obtaining accurate education about pregnancy due to limitations in time, location, and access to medical professionals. Puskesmas, as a primary healthcare center, plays a crucial role but is limited by the number of healthcare workers and operational hours, reducing the effectiveness of maternal health education delivery. Therefore, AI-powered chatbots can provide instant, personalized information that can be accessed anytime and anywhere. In this study, the developed chatbot using the RNN algorithm is capable of processing conversations contextually, providing relevant answers according to the stage of pregnancy and the specific needs of the pregnant woman. The implementation of this chatbot at Puskesmas Kota Rantauprapat is expected to improve the accessibility of maternal health education, reduce anxiety among pregnant women, and minimize the need for physical visits for common questions. The results of this study demonstrate the potential of RNN-based chatbots as an efficient tool in supporting maternal health education through digital platforms.